Application of Number Head Together (NTH) Learning Method in Mathematical Learning in Inclusive Settings in Class IV SDN 100 Cipedes, Bandung City - Surya, Havid; Assjari, Musjafak (International Conference on Elementary Education, 2020)
Currently, inclusive education is a common spirit and studies will continue to focus on examining the mathematics learning process that aims to find out the abilities, obstacles, and needs of children who experience mathematical obstacles in Class IV SDN 100 Cipedes in inclusive settings. By aligning the existing curriculum the assessment process is carried out to look for data about the existence of mathematical learning abilities of students who experience mathematics learning barriers so that students who have difficulty learning mathematics are known to their obstacles, abilities, and needs. From the results of the cooperative learning model assessment model with the Number Head Together type selected in the process of learning mathematics in an inclusive setting because it is a cooperative learning activity with four stages of activity. First, students are grouped into several groups, each group member is given one number 1,2,3, and 4. Second, the teacher gives questions or questions to all groups. Third, students discuss and convince team members to understand the team's answers